Efektivitas Tatalaksana Aplikasi Smartphone dan Non Smartphone terhadap Regulasi Glikemik (Kadar Gula Darah dan Hba1c) pada pasien Diabetes: A Systematic Review - Tifanny Gita Sesaria; Kusnanto Kusnanto; Abu Bakar (FORIKES, 2021)
Background: Diabetes mellitus (DM) is a chronic disease that is a global public health problem that has a social impact, economic impact, and quality of life for patients, which leads to increased morbidity and mortality. Uncontrolled blood sugar levels and long-term DM, affecting the pathophysiology of disorders including diabetic retinopathy, heart disease, kidney failure, hyperglycemia and hypoglycemia are needed interventions that can help regulate glycemic (blood sugar levels and HbA1c). Objective: To find out various therapies non-smartphone and smarthphone to regulate glycaemic control (blood glucose and hba1c) in patients with diabetes mellitus. Method: This systematic review was based on preferred reporting items for systematic reviews and meta-analyzes (prisma). The database used in this studied was scopus, proquest and pubmed were limited to the last 5 years of publication from 2015 to 2020 and full-text article. The keywords used were